The Emergence of a Greek-Turkish Cooperation System as the Result of a “Butterfly Effect” - Vathakou, Eugenia (Études helléniques / Hellenic Studies, 2007)
By employing Niklas Luhmann's modern systems theory, this article discusses how an accidental event, a natural disaster such as the devastating earthquake that occurred in Turkey in 1999, could have a “butterfly effect”, namely trigger a chain of changes, which led to the emergence of a system of Greek-Turkish co-operation. To this end, it explores not only the role different social systems, such as the media, diplomacy, civil society organizations and politics can play in conflict transformation, but it also sheds light to the role contingency and chance can play. The article's main argument is that the new emerging order, the system of Greek-Turkish cooperation, was constituted through a causal process and it was not the result of a rational decision making process. The research conducted reveals the blind spots of social systems which contributed to the constitution of this emerging order and yet they could not see and control their contribution into it. The article is based on fieldwork conducted in Turkey and Greece and involves primary source material gathered through more than 20 interviews with Greek and Turkish politicians, diplomats, academics, journalists and civil society representatives.